60. Calculation of kQ factors for reference ionization chambers following the recent recommendations on basic data for ionizing-radiation dosimetry. (December 2018) - Pimpinella, M.; Silvi, L.; Pinto, M.
Abstract : Purpose: The International Commission on Radiation Units and Measurements (ICRU) in the Report 90[1] has recommended adoption of new values for key data required for ionizing radiation dosimetry. In the framework of the EMPIR RTNORM project "kQ factors in modern external beam radiotherapy applications to update IAEA TRS 398", beam quality correction factors, kQ, for reference dosimetry in high energy photon beams are calculated using the ICRU 90 basic data. Methods: The ICRU 90 compliant EGSnrc Monte Carlo code is used to calculate kQ factors using new values for the mean excitation energies (I) for air, graphite, and water, renormalized photoelectric cross-sections and the crystalline density for graphite when evaluating the density effect (δ). Since the NE 2571 Farmer ionization chamber has long been studied, calculations were made first for this chamber so to select the most appropriate simulation parameters and techniques. The ionization chamber was modelled in details using the EGSnrc C++ geometry package and absorbed doses to the air cavity and to water were calculated using the egs _ chamber user code with a target statistical uncertainty below 0.1%. Simulations were run in parallel using the ENEA CRESCO4 cluster. Results: NE 2571 simulations for Co-60 and 6 MV to 25 MV photon beams showed that, while adoption of renormalized photoelectric cross-sections did not affect calculation results, variations in absorbed dose to the air cavity and absorbed dose to water due to the update of I and δ values were up to 0.5% and 0.2%, respectively. Nevertheless, changes partially offset each other and the overall effect on kQ values was below 0.2%. Work is in progress for other widely used ionization chambers. Conclusions: In the range 6–25 MV ( TPR 20, 10 of photon beams from 0.663 to 0.80), the calculated values of kQ for the NE 2571 ionization chamber tend to be lower than the current values in the IAEA TRS 398 protocol with differences up to about 0.5% at the highest TPR 20, 10 values.